Optimum stage of harvest for extraction of total withanolides in aswagandh (Withania somnifera Dunal) - BALAKRISHNAMURTHY, D MUTHUMANICKAM, G (Journal of Spices and Aromatic Crops, 1999)
Aswagandh (Witkania somnifera Dunaj) is an important medicinal plant grown in India. The leaves, stems and roots of the plant contain withanolides and steriodallactones, which exhibit marked activity againt various diseases especially, bacterial infections in human beings.